The metabolomic profile of red non-V. vinifera genotypes. (August 2017) - Ruocco, Silvia; Stefanini, Marco; Stanstrup, Jan; Perenzoni, Daniele; Mattivi, Fulvio; Vrhovsek, Urska
Abstract: Wild American genotypes represent an important part of the Vitis germplasm in relation to grape improvement. Today, these genotypes are currently involved in breeding programmes in order to introgress traits resistant to pests and diseases in V. vinifera cultivars. Nevertheless, the metabolic composition of their grapes has not been widely investigated. This study aimed to explore in detail the metabolomic profile in terms of simple phenolic, proanthocyanidin, anthocyanin and lipid compounds in two hybrids and five American genotypes. The results were compared with those of two V. vinifera cultivars. A multi-targeted metabolomics approach using a combination of LC-MS and LC-DAD methods was used to identify and quantify 124 selected metabolites. The genotypes studied showed considerable variability in the metabolomic profile according to the grape composition of V. vinifera and other Vitis genotypes. As regards the composition of anthocyanins, not all wild genotypes contained both mono- and di-glucoside derivatives. Wild genotype 41B and V. vinifera cultivars contained only monoglucoside anthocyanins. The proanthocyanidins of non- V. vinifera genotypes were mainly rich in oligomers and short-chain polymers. The analysis of lipids in wild Vitis genotypes, here reported for the first time, showed the existence of a certain diversity in their composition suggesting a strong influence of the environmental conditions on the general lipid pattern. Abstract : Graphical abstract Highlights: The composition of simple phenols, anthocyanins, proanthocyanidins and lipids was studied. Uni- and multi-variate analyses were used to evaluate similarities in metabolite composition in the evaluated genotypes. Genetic variation greatly influenced the clustering patterns of simple phenolics, proanthocyanidins and anthocyanins. Environmental conditions conceivably affected the general lipid pattern.